Lecotec: a extensão universitária como fator de diálogo com o ensino, a pesquisa e as práticas profissionais - Cruz Junior, Jonas Lírio [UNESP]; Carrijo, Fabiane Fernandes [UNESP]; Miranda, Giovani Vieira [UNESP]; Carvalho, Juliano Maurício de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The University Extension Programs provide an unique social contribution by promoting a bilateral dialogue between academic research and community, as well as, by offering to students an experience directly related to its professional activities. Based on these values, the Laboratory for Communication, Technology and Citizenship Education (LECOTEC) has been investing and empowering its extension bases focused on Communication, Creative Industry, and Media and Technology. Among the activities offered by the laboratory are projects like Unesp Reporter and Creative Industry Observatory, which now work under the same resolution and objectives. Furthermore, the laboratory offers for its members and community the dissemination of its productions and outcomes bimonthly seminars that aim to create a proper environment for the exchange of interest data and social appliances. Over the palpable optimization of contributors and processes, the LECOTEC has been gathering experimental digital structures that intensify interdisciplinary activities for the production, dissemination and debate of content that are expected from the university extension projects.

A extensão universitária pode ser observada como um elemento necessário para a promoção do diálogo entre as dimensões de ensino e pesquisa, bem como ser uma ponte para o contato com experiências diretamente relacionadas com a formação profissional. É com base nessa premissa que o Laboratório de Estudos em Comunicação, Tecnologia e Educação Cidadã (Lecotec) tem promovido ações para o fortalecimento de suas bases de extensão com foco nas temáticas de Comunicação, Indústrias Criativas, e Mídia e Tecnologia. Tal meta vem sendo estabelecida a partir da junção das ações e objetivos dos projetos “Repórter Unesp” e “Observatório de Indústrias Criativas” além da disseminação dos resultados e análise das metas coletivas por meio da realização de Colóquios bimestrais. Com a evidente otimização das equipes e processos, o Lecotec tem agregado estruturas digitais experimentais que propiciam atividades interdisciplinares e intercursos para a produção, difusão e debate de conteúdos a partir da extensão.
Keywords: Communication; Media and technology; Creative industries; Comunicação; Mídia e tecnologia; Indústrias criativas